Effect of Al Electrodes on Surface Passivation of TiOx Selective Heterocontacts for Si Solar Cells. Issue 3 (26th October 2022) - Liang, Wensheng; Narangari, Parvathala; Tong, Jingnan; Michel, Jesus Ibarra; Murdoch, Billy J.; Sio, Hang Cheong; Kho, Teng; Kremer, Felipe; Armand, Stephane; McIntosh, Keith; Bullock, James; Fong, Kean Chern
Abstract : This article presents a comprehensive study regarding the impact of the Al electrode on the surface passivation of three TiO x ‐based passivating selective contacts: TiO x :Al/LiF x /Al, TiO x /LiF x /Al, and a‐Si/TiO x :Al/LiF x /Al. A deterioration in passivation is recorded after the deposition of the Al electrode at close to room temperature, where the deterioration correlated to the Al thickness. A thin Al (10 nm) electrode resulted in the most severe passivation decline, while samples with a 100 nm Al electrode showed much less passivation deterioration. Furthermore, it is found that a low‐temperature annealing step led to a partial recovery of the passivation, particularly in the case of TiO x :Al/LiF x /Al and a‐Si/TiO x :Al/LiF x /Al contacts. The presented discovery in this article provides crucial insight into the importance of characterization and evaluation of passivating contacts, which is demonstrated here to be highly sensitive to the deposited metal thickness and the interfacial layers, as well as to the post‐deposition annealing. Abstract : This article addresses that the Al electrode is able to damage the thin TiO x passivation layer even at room temperature, resulting in significant passivation deterioration following metallization. The deterioration is correlated to the Al thickness and thermal treatments. Doping TiO x with Al or inserting an interfacial layer (LiF x ) is effective to inhibit the damage of TiO x from Al electrode.